Pengaruh Kemampuan Membaca dan Minat Belajar Terhadap Hasil Belajar Siswa pada Pembelajaran Bahasa Indonesia - Supriyadi, Arif; Olpisrianasro, Olpisrianasro (Pedagogik: Jurnal Pendidikan, 2024)
Students' reading ability and interest in learning are the primary keys to good learning results. The ability to read is essential to support student learning outcomes. The more fluently students read and are interested in learning, the better the students' learning outcomes will be in understanding the lesson. This research aims to determine whether reading ability and interest in learning influence student learning outcomes in class V Indonesian language learning at State Elementary School 8 Langkai Palangka Raya. The research method used is quantitative. The data collection techniques used were questionnaires and tests. The research results show that reading ability influences student learning outcomes in class V Indonesian language learning at State Elementary School 8 Langkai Palangka Raya by 77.2%. Meanwhile, the remaining 22.8% is influenced by other factors that are not included in the model or are not being researched. This influence is proven by the t-count results in the ANOVA table of 9.732 with a significance of 0.000 <0.05. Interest in learning influences student learning outcomes in class V Indonesian language learning at State Elementary School 8 Langkai Palangka Raya by 25.1%. Meanwhile, the remaining 74.9% is influenced by other factors that are not included in the model or are not being researched. This influence is proven by the t-count results in the ANOVA table of 3.063 with a significance of 0.005 < 0.05. Reading ability and interest in learning influence student learning outcomes in class V Indonesian language learning at SDN 8 Langkai Palangka Raya by 82%. Meanwhile, the remaining 18% is influenced by other factors that are not included in the model or are not being researched. This influence is proven by the Fcount results in the ANOVA table of 61.491 with a significance value 0.000.